THE READINESS OF MITIGATION PLAN FOR URBAN CITY TOURISM IN JAKARTA: AN EXPLORATORY STUDY ON BIG HOTEL CHAINS - MATTHEW PRASETYA IHSAN (Fakultas Pariwisata Universitas Pancasila, 2021)
Tourism Industry is one of the biggest industry in the world, especially in Indonesia, tourism has contributed one of the highest earners for the country, but in the third quarter of 2019 the world was faced with a global health threat which results in the lost of tourism income throughout the world due to the regulation and health protocol that were used in order to maintain the worlds stability of health danger, due to the current situation, tourism were highly impacted and hotel industry are one of the most part that were hit hard, that why the purpose of this study is to investigate the mitigation plan readiness of the hospitality industry in Jakarta, focusing on top hotel chains, the readiness. Secondary data collection are used in this research, using desk research from hotel chains latest updated websites in the field of risk management and mitigation plan available. From the research it is found that the Hospitality Industry especially hotels in Indonesia are exposed to crisis, it is becoming increasingly important of having its own mitigation plan and communicating it well to the stakeholders due to the recent pandemic that leads to a lot of loses in the industry, thus not all the hotel chains in Indonesia have communicated their mitigation well to their guest through one of the important communication platform of the hotel which is their official website. In its current iteration, the time was a major limitation and also there is not much research regarding the situation in Indonesia. The study was conducted using secondary data with desk-research method through online data available, which are limited towards the public. Practitioners, researchers and internal stakeholders in the hospitality industry will find the implications of this study useful in the context of the present complex hospitality environment which is fraught with risks. This study is a part of a larger project where the research team is investigating readiness of mitigation plan in the hospitality industry in Indonesia focusing on hotel chains